Logic of the sublime. Deleuze, Kant and the genesis of value (Itinera, 2021)
The article discusses some aspects of Deleuze’s reinterpretation of Kantian aesthetics, specially focusing on the theme of the sublime with a twofold goal. On the one hand, it is showed how Deleuze elaborates a theory of thought criticizing some implicit presuppositions of Kantism: i.e., the common sense and the agreement of the faculties. In that context, the critique of the “recognition” model takes on a special function in order to clarify the dynamics of the sublime. On the other, it is a matter of investigating the ethical theme marking the sublime experience: a moment where the disagreement of cognitive faculties gives rise to new values unrecognized and unrecognizable. By stimulating that disagreement of the faculties, sublime thus allows us to express and scrutinize, on the Kantian side, a theme Deleuze had already encountered in Nietzsche’s thought: the creation of values.
Keywords: Deleuze, Kant, Sublime, Values, Moral